Effects of a Short Video Physical Activity Program on Physical Fitness Among Physical Education Students. Issue 3 (June 2022) - Bulca, Yeşim; Bilgin, Emre; Altay, Figen; Demirhan, Gıyasettin
The Brain Break (BB) short video program is designed to improve physical activity (PA), motor skills, and fitness in children. In this study, we examined the effects of an 8-week short video-based Brain Break (HOPSports Company) PA program within physical education (PE) lessons on fitness and fitness knowledge among students. We studied 62 fifth-grade students (experimental group = 28; control group = 34) in the Ankara, Turkey school district. The experimental group received PE lessons once per week for eight weeks with the BB PA program, with extra videos viewed at home three days per week, while the control group received routine PE lessons during this period. We collected student responses to the Fitness Knowledge Test for Children and the Fitnessgram Test Battery before and after the experimental BB program. Results revealed that the experimental group showed increased fitness and fitness knowledge compared to the control group, showing that the BB PA videos can increase fitness and fitness knowledge in students.